Understanding the effectiveness of using tags in social media query management - a perspective from X Solutions Limited - Rahat, Raihan Alam (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.